Faça você mesmo: punk e moda pelos fios da memória de Vivienne Westwood (1971-1985) - Costa, Grace Campos (2022)
The research aims to understand the punk aesthetic from the perspective of Vivien Westwood and understand how it dialogues with street and youth fashion and puts it on the catwalks. For this, we analyze not only Westwood's trajectory, but also that of his ex-partner, Malcolm McLaren, based on their artistic references. Finally, we will see the importance of MTV for the discovery of fashion and how the channel was important for the stylist's career.